Modification of precipitated calcium carbonate with cellulose esters and use as filler in papermaking - Gamelas, José A. F. (2014)
New hybrid materials of precipitated calcium carbonate (PCC) and cellulose esters (cellulose acetate and cellulose acetate butyrate) were prepared aiming to obtain new modified fillers for papermaking. A novel simple procedure based on the mixing of an aqueous suspension of PCC with an organic solution of the cellulose derivative, followed by the addition of the resultant mixture to hot water, was followed. The hybrids were characterized by several analytical and spectroscopic techniques. The organics content in the hybrids determined based on the carbon elemental analysis or by thermogravimetry, was found to be of ca. 10 wt%. Due to the presence of the organics the average size of the particles increased slightly in comparison to the unmodified PCC. Results of the modified PCCs as fillers in papermaking showed a slight improvement of some paper strength properties, whereas the structural and optical properties were not affected.